2007
DOI: 10.1007/s00531-007-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

Variability in upwelling intensity and nutrient regime in the coastal upwelling system offshore Namibia: results from sediment archives

Abstract: The coastal upwelling system offshore Namibia is ideally suited to address a focal question of the Integrated Marine Biogeochemistry and Ecosystem Research Programme: what are the mechanisms that drive long-term changes in ecosystems? Considerable interannual variability in climatic forcing is indicated by long time series of meteorological and remote sensing observation; these accompany considerable interannual to interdecadal changes in the upwelling intensity over the last 100 years, as well as a centennial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 58 publications
(72 reference statements)
1
34
0
1
Order By: Relevance
“…There has been not-too-convincing evidence of mutidecadal changes in wind intensity in the south subtropical Atlantic. A St Helena Climate index, which apparently reflects the intensity of the southeasterly trades in the South Atlantic, shows strengthening from 1900 to the 1930s, weakening to stable conditions to the 1970s and then a weak strengthening from the 1980s to 2000 [57]. Despite the apparently weak St Helena Climate trends, upwelling intensity followed the expected patterns.…”
Section: Oscillations In Gyre Circulation and Upwellingmentioning
confidence: 80%
“…There has been not-too-convincing evidence of mutidecadal changes in wind intensity in the south subtropical Atlantic. A St Helena Climate index, which apparently reflects the intensity of the southeasterly trades in the South Atlantic, shows strengthening from 1900 to the 1930s, weakening to stable conditions to the 1970s and then a weak strengthening from the 1980s to 2000 [57]. Despite the apparently weak St Helena Climate trends, upwelling intensity followed the expected patterns.…”
Section: Oscillations In Gyre Circulation and Upwellingmentioning
confidence: 80%
“…Second, the central Namibian shelf exhibits pronounced nitrate deficits in coastal proximity (Tyrrell & Lucas 2002;Kuypers et al 2005). The nitrate deficits (i) in combination with the coastal-parallel belt of high d (Figs 4A, 5), and the oxygen depletion in the bottom waters (iv), unanimously support the influence of denitrification in the source waters (see also Pichevin et al 2005;Emeis et al 2009;Lavik et al 2009). Based on a number of nutrient profiles taken at selected stations during Meteor cruise M57-3, Brçchert et al (2004) were able to locate the zones of denitrification along the water column.…”
mentioning
confidence: 80%
“…(Villareal et al 1993) and (iii), according to the concept of Rayleigh fractionation kinetics, abundant nitrate supply. To our knowledge, no evidence has yet been found that nitrogen fixation plays an important role in the area investigated (see also Emeis et al 2009). The same applies to vertically migrating diatoms.…”
mentioning
confidence: 96%
See 2 more Smart Citations